Shift patterns of internal bacterial communities across five life stages of laboratory-maintained Eremobelba eharai (Acari: Oribatida: Eremobelbidae) - Chen, Yu; Chen, Jun (Frontiers in Microbiology, 2025)
Microbial communities play a crucial role in the physiological characteristics, adaptability, and reproductive success of arthropods. However, the patterns and functions of microbial variation across different life stages of mites remain poorly understood. In this study, we used high throughput Illumina sequencing of the 16S rRNA gene to investigate the composition and functional potential of bacterial communities in five life stages (larva, protonymph, deutonymph, tritonymph, and adult) of the oribatid mite Eremobelba eharai. We found significant differences in bacterial diversity and community structure across the different life stages despite being fed the same diet. The bacterial diversity was highest at the protonymph stage and lowest at the tritonymph stage. Beta diversity analysis indicated distinct bacterial community compositions among the different life stages. Bacteroidota, Proteobacteria, and Firmicutes dominated the bacterial communities throughout the host's life cycle. Key bacterial genera, such as Bacillus, Streptomyces, Achromobacter, and Tsukamurella, showed significant differences in abundance across the different life stages. Predicted functional profiles revealed substantial changes in metabolic pathways, which may reflect changes in the nutritional needs of E. eharai during its developmental process. PICRUSt prediction results also showed that in most KEGG pathways, the larval and adult stages consistently maintain similar relative abundances of bacteria. Different stages such as the deutonymph and adult stages show consistent differences in the “biosynthesis of other secondary metabolites” and “glycan biosynthesis and metabolism” pathways. This study provides new insights into the dynamic changes of bacterial communities within oribatid mites and lays a foundation for further research on the interactions between oribatid mites and microorganisms.